Pemanfaatan Saluran Irigasi sebagai Pembangkit Listrik Tenaga Air (VORTEX) untuk Daerah Tidak Terdampak Pasokan Listrik PLN - Muhammad Hasan Basri; Rahmat Rizky; Alfin Febrianto; Annasrullah Annasrullah; Aminuddin Aminuddin; As’Aad Bayu Ramadhan; Ahmad Albar Ramadhan; Yoga Kiani Awk; M. Badrus Zaman; M. Alvin Aris V; Anwar Zamani; Burhanudddin Burhanudddin (Universitas Nurul Jadid, 2021)
Duren village, ivory sub-district, located in the mountainous area south of Probolinggo Regency, is one of the mountainous villages that has limited electricity supply or has not yet received electricity supply from PLN. Because they have not yet received electricity supply from PLN, the local community uses the irrigation channel as a vortex power plant. Where the area of Duren village is very possible to make a vortex power plant because the irrigation canal is very suitable as a manufacturing location. With the existence of a whirlpool (vortex) power plant, it can alleviate the community of Duren village due to the electricity needs that have not received electricity supply from PLN. Results obtained from channel utilization activities a whirlpool (Vortex) irrigation power plant in the village of Duren areIncreased public knowledge about Vortex Before installing the equipment, first hold a meeting with community leaders in Duren village to determine the important places or facilities to install the equipment. At the installation location and an explanation of the Vortex to the responsible citizen. Instructions are also given directly to those who are given the task of operating the equipment on a daily basis at the time of installation. From this activity it is known that the community does not know how to properly care for and maintain the whirlpool power plant facilities. The material presented was about the basic principles of Vortex and continued with installation and maintenance procedures.